Penerapan Model Pembelajaran Kooperatif Make A Match Untuk Meningkatkan Hasil Belajar Kognitif Biologi Siswa Kelas XI di Madrasah Aliyah Madani Pao-Pao Kabupaten Gowa - H, Herlina; Purnamasari, A. Bida (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is a classroom action research (PTK) or commonly referred to as Classroom Action Research with the objective that the research can improve the cognitive learning outcomes of students through the application of Make a Match cooperative learning model of grade XI students. The research subjects consisted of 40 students with the implementation stage carried out two cycles (Cycle I and Cycle II), as for the data obtained were analyzed using quantitative descriptive analysis. The results of the study show that the application of Make a match type cooperative learning model can improve the cognitive learning performance of students of class XI.a Aliyah Madani Pao-pao Madrasah of Gowa District. The improvement was shown from the research results of cycle I to cycle II, namely the mean score of students’ cognitive learning outcome increased from 56.00 to 67.70 and the increase in the percentage of students who completed from 47.50 % to 87.50%. Based on the results of the quantitative analysis an improvement was obtained for students’ cognitive learning performance on excretory system material in cycle I and cycle II by 40% thus it can be concluded that there was an improvement in the cognitive learning performance of students of grade XI.a Aliyah Madani Madrasah Pao-pao Gowa District.